Finite-Size Scaling Approach for Critical Wetting: Rationalization in Terms of a Bulk Transition with an Order Parameter Exponent Equal to Zero - Albano, Ezequiel Vicente (2012)
Clarification of critical wetting with short-range forces by simulations has been hampered by the lack of accurate methods to locate where the transition occurs. We solve this problem by developing an anisotropic finite-size scaling approach and show that then the wetting transition is a ‘‘bulk’’ critical phenomenon with order parameter exponent equal to zero. For the Ising model in two dimensions, known exact results are straightforwardly reproduced. In three dimensions, it is shown that previous estimates for the location of the transition need revision, but the conclusions about a slow crossover away from meanfield behavior remain unaltered.